Idelalisib in Combination With Rituximab or Bendamustine or Both in Patients With Relapsed/Refractory Chronic Lymphocytic Leukemia - Coutre, Steven E. (Hemasphere, 2018)
Phosphatidylinositol 3-kinase-delta (PI3Kδ) signaling is critical for proliferation, survival, homing, and tissue retention of malignant B cells. Idelalisib, a selective oral inhibitor of PI3Kδ, has shown considerable single-agent activity in patients with heavily pretreated chronic lymphocytic leukemia (CLL). This study evaluated the safety and clinical activity of idelalisib in combination with bendamustine (IB) or rituximab (IR) or both (IBR) in patients with relapsed or refractory (R/R) CLL. Idelalisib was given continuously at 100 or 150 mg twice daily in combination with rituximab (375 mg/m(2) weekly × 8 doses), bendamustine (70 or 90 mg/m(2), days 1 and 2 every 4 weeks × 6 cycles) or BR (rituximab, 375 mg/m(2) every 4 weeks and bendamustine, 70 mg/m(2), days 1 and 2 every 4 weeks × 6 cycles). The primary endpoint was safety; secondary endpoints included overall response rate (ORR), duration of response (DOR), and progression-free survival (PFS). Fifty-two patients (median age 64 years) with a median of 3 prior therapies were enrolled. ORR was 84.6% (89.5% IR group, 77.8% IB group, and 86.7% IBR group). The overall median PFS was 25.6 months, and median DOR was 26.6 months. The most common grade ≥3 adverse events (≥10% of patients) were pneumonia (19.2%), diarrhea (13.5%), and febrile neutropenia (17.3%). Idelalisib-based combination therapy with bendamustine and/or rituximab was highly active, resulting in durable tumor control in patients with heavily pretreated R/R CLL. However, its tolerability profile suggests that these regimens should be used cautiously in this patient population. ClinicalTrials.gov ID: NCT01088048.